Extremely rare cause of extrinsic compression of the stomach during esophagogastroduodenoscopy - Işıl Başara Akın; Canan Altay; Göksel Bengi; Oktay Tarhan; Mustafa Seçil (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Başara Akın I, Altay C, Bengi G, Tarhan O, Seçil M. Extremely rare cause of extrinsic compression of the stomach during esophagogastroduodenoscopy. Turk J Gastroenterol 2019; 30(12): 1064-5.